(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper proposes a study of the effect of exercise on divergent thinking in secondary school students. The work is in the nature of a preliminary study of the problem, since it was carried out with a small number of high school students. It was important for us to conduct this study in order to ensure the reliability of the method used. Based on this test work, our research group will do a similar work with a more expanded number of private traders and experimental schools in general.